NEW EXPLICIT WAVE PROFILES OF KUNDU-MUKHERJEE-NASKAR EQUATION THROUGH JACOBI ELLIPTIC FUNCTION EXPANSION METHOD - Tarla, Sibel; Ali, Karmina K.; Yusuf, Abdullahi; Yilmazer, Resat; Alquran, Marwan (Editura Acad Romane, 2022)
In this paper, the Jacobi elliptic function expansion approach is used to explore the Kundu-Mukherjee-Naskar equation, which describes the fiber pulse in optics, rogue waves in the seas, and light beam bending. As a consequence, many structures of solutions based on the parameter module m, such as optical dark-bright, dark, bright, singular, Jacobi elliptic function, and exponential solutions, have been effectively developed. In the solutions produced to analyze wave propagation, specific values for free parameters are presented. We also used computer tools to display 3D surfaces, 2D images, and contour plots of some of the created solutions. To our knowledge, all the obtained solutions verify the partial differential equation.
Keywords: Kundu-Mukherjee-Naskar equation; Jacobi elliptic function expansion method; Solitons.